Rib‐reinforced Shell Structure - Li, Wei; Zheng, Anzong; You, Lihua; Yang, Xiaosong; Zhang, Jianjun; Liu, Ligang (Computer graphics forum, 2017)
Shell structures are extensively used in engineering due to their efficient load‐carrying capacity relative to material volume. However, large‐span shells require additional supporting structures to strengthen fragile regions. The problem of designing optimal stiffeners is therefore becoming a major challenge for shell applications. To address it, we propose a computational framework to design and optimize rib layout on arbitrary shell to improve the overall structural stiffness and mechanical performance. The essential of our method is to place ribs along the principal stress lines which reflect paths of material continuity and indicates trajectories of internal forces. Given a surface and user‐specified external loads, we perform a Finite Element Analysis. Using the resulting principal stress field, we generate a quad‐mesh whose edges align with this cross field. Then we extract an initial rib network from the quad‐mesh. After simplifying rib network by removing ribs with little contribution, we perform a rib flow optimization which allows ribs to swing on surface to further adjust rib distribution. Finally, we optimize rib cross‐section to maximally reduce material usage while achieving certain structural stiffness requirements. We demonstrate that our rib‐reinforced shell structures achieve good static performances. And experimental results by 3D printed objects show the effectiveness of our method.